Unpacking adolescent masculinity: relations between boys' sexual harassment victimization, perpetration, and gender role beliefs - Rizzo, Andrew J. (Journal of family violence, 2021)
Adherence to rigid masculine gender role beliefs is often a significant predictor of violence perpetration; additionally, there is a consistent link among adolescent boys between experiencing victimization and perpetrating violence. This study examines the nuances in those associations specifically for sexual harassment victimization, perpetration, and masculine gender role beliefs in a rural sample of adolescent boys. A convenience sample of 236 boys’ responses to an electronic survey completed at school were examined using multiple regression analysis to explore the relation of perpetration with victimization and four gender-related attitudes, specifically male power, relationship control, acceptability of violence, and apathy toward others. Consistent with prior research, victimization was strongly related to perpetration; however, this link was true only when attitudes on male power and apathy toward others were also high. Findings indicate that certain attitudes within hegemonic masculinity may be more involved than other beliefs in the victim-to-perpetration adolescent violence cycle. Prevention programming that incorporates content on masculinity may be more effective if focused intentionally on these aspects of gender role beliefs. Implications are also discussed in the context of how rural boys may engage with ideas of masculinity.